A Retrospective Study of the Profile and Outcome of Children with Dravet Syndrome in a Tertiary Care Hospital of Southern India - Banerjee, Bidisha; Prabhu, Sameeta M.; Lagudu, Gowthami; Shetty, Mitesh; Hegde, Sridevi (Journal of Pediatric Epilepsy, 2022)
Objective Dravet syndrome (DS) is an epileptic syndrome that shares similarities with febrile seizures (FS), especially before 1 year of age, making it challenging to differentiate the two. We describe the profile of DS, with emphasis on the first year of life that can aid in early diagnosis.Methods The clinical, investigative, treatment, and outcome profiles of DS patients presenting to the outpatient department (OPD) between October 2016 and December 2021 in a single tertiary care center in South India were analyzed.Results Seventeen children were studied, with median age at presentation of 30 (interquartile range [IQR] 10, 47) months. The median age at seizure onset was 5 (IQR 3, 6) months. First seizure semiology were generalized tonic-clonic (GTCS) (35.3%), focal (52.9%), and myoclonic (11.8%). Fever preceding first seizure was seen in 76.5%. Status epilepticus (SE; ≥30 minutes) and prolonged seizures (>10 minutes) were seen in 41.2% each, and >5 seizures were seen in 82.4% in the first year of life. The most frequent subsequent seizure types were focal seizures (76.5%) and GTCS (76.5%). Other seizure triggers included vaccination (52.9%), light (17.6%), and Hot-bath (5.8%). Delayed developmental milestones for age were found in 52.9% at diagnosis. Magnetic resonance imaging (MRI) brain and electroencephalogram were normal in 76.4% each. Pathogenic/likely pathogenic variants in SCN1A gene were seen in 64.7%. Average of 3.9 anti-seizure medications were used. After optimization of treatment seizure frequency reduced in 40% and 4/15 (26.6%) had SE.Conclusion In addition to characteristic clinical profile of DS we observed atypical presentations: an earlier age of seizure onset and afebrile seizure at onset. Delayed diagnosis was noted. Seizure control improved and SE reduced on optimal treatment.
Keywords: Dravet syndrome; infancy; epileptic syndrome; drug refractory; SCN1A